SAP Dispute Management implementation - Mäenpää, Maria (My University, 2012)
Research questions concentrate on finding answers how the case company will benefit and what challenges there can be when implementing SAP Dispute Management tool. Research is also based on how to impact the whole order to cash process and making it more effective to prevent disputes. The idea is to take advantage of SAP Dispute Management and learn from its results and teach end-users to learn from disputes‟ reasons and find away to minimize them. Research goes through the importance of Customer Relationship Management and process improvement methods which can be used to improve processes to prevent dispute increase. Research presents the logic of SAP Dispute Management and how to control dispute cases. SAP Dispute Management implementation has been described through a global case company. Answers to the research questions were find through end-users‟ interviews before and after SAP Dispute Management implementation. Research used Balanced Critical Factor Index method and send questionnaire to end users. There are also results of my personal observation based on training of the end-users and from the feedback I have received. Research showed that the most important benefit in implementation was to have the transparency of the dispute cases through the whole company. Another result is that most commonly used reason code in disputes has been the code: Missing payment.
Keywords: Asiakkuuden hallinta; taloudellinen toimitusketjun hallinta; riidan hallinta; fi=Tuotantotalous|en=Industrial Management|